Mapping a way forward for the decriminalisation of sex work in South Africa : the case for an intersectional and rights-based approach to regulation - Jooste, Yvonne (University of Pretoria, 2025)
Dissertation (MPhil (Jurisprudence))--University of Pretoria, 2025.